Low awareness of HPV infection and willingness of HPV vaccination among Chinese male college students in the east of China - Ran, Hu; Chen, Yue; Gao, Jun; Guo, Hongxiong; Peng, Shanshan (Frontiers in Public Health, 2022)
Introduction Human Papillomavirus (HPV) vaccine has proven to play a major role in preventing sexually transmitted diseases and related cancers among both men and women. However, the coverage of the HPV vaccination is still limited. Objective The study aims to evaluate the awareness of HPV and HPV vaccine, as well as the willingness to take HPV vaccine, especially factors influencing vaccination willingness among male college students. Methods We conducted a cross-sectional investigation among male college students from six colleges in Jiangsu, China. A structured questionnaire was used to investigate the subjects' basic information, behavior habits, cognition of the HPV vaccine, and intention for HPV vaccination. Multivariate analysis modes were used to analyze the influencing factors of vaccine awareness and willingness. Results We found that among 912 participants, only 24.34% of the participants had a “good knowledge” of HPV and HPV vaccine, and 34.54% showed a “positive attitude“ toward the HPV vaccine after obtaining knowledge of HPV and its vaccine. Factors such as immune persistence, side effects, pricing strategy, and participants' self-assessment of HPV infection were the main factors influencing the HPV vaccination. Conclusion Strengthening health education on the HPV vaccination and finding appropriate ways to solve the problem of ”vaccine hesitancy“ will be effective in improving the coverage of the HPV vaccine and preventing related diseases. In addition, the lifting of restrictions on HPV vaccination for men in China may also prove useful.